J chain synthesis and ultrastructural changes in chronic lymphocytic leukaemia cells during in vitro differentiation. - Yasuda, N (1984)
The synthesis of J chain and the ultrastructural changes in chronic lymphocytic leukaemia (CLL) cells during in vitro cultures stimulated with PWM and/or allogenic T cells were investigated by immunoelectron microscopy, radioimmunoassay and anti-idiotype antibodies, in an attempt to demonstrate changes in the maturation stage of CLL cells. The cells from four patients showed the induction of J chain synthesis in parallel with the increase of Ig synthesis. Two of revealed cytological transformations, in which CLL cells resembled immunoblasts or plasmacytoid cells. These findings suggest that some CLL cells are not 'frozen' within the original maturation stage and can be induced to differentiate to a more mature stage.